BiSbS3@N-doped carbon core–shell nanorods as efficient anode materials for sodium-ion batteries. Issue 28 (24th June 2019) - Wen, Siying; Zhao, Jiachang; Chen, Jiajun; Yang, Jingxia; Xu, Jingli
Abstract : BiSbS3 @N-doped carbon (NC) core–shell nanorods were prepared through a simple preparation process. Abstract : BiSbS3 @N-doped carbon (NC) core–shell nanorods were prepared through a simple preparation process. As anode materials for sodium-ion batteries (SIBs), BiSbS3 @NC core–shell nanorods present excellent electrochemical performance with higher specific capacity and better rate capability compared with the unmodified pristine BiSbS3 nanorods. The BiSbS3 @NC electrode delivers high sodium storage capacity (771.5 mA h g −1 in the 2 nd cycle) and excellent rate performance (capacity of 518.4 mA h g −1 at 1000 mA g −1 ). The improvement in electrochemical performance results from the coated conductive NC layer which brings about fast ion/electron transfer and buffers volume expansion. The BiSbS3 @NC core–shell nanorods are thus promising high performance anode materials for SIBs.